Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Return On Asset Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia Periode 2017-2020 - Nurfitriana; Edi Yanto; Anita Aprilia (Jurnal Simki Economic, 2021)
This type of research uses a quantitative descriptive approach to answer problems related to the effect of cash turnover and receivables turnover on return on assets in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. Through the results of statistical tests with the help of SPSS software, it was found that: (1) The cash turnover variable had a significant level of 0.039 > 0.05 and a tcount value of -2.107. of 1.67022 so that it can be obtained that tcount < ttable (-2.107 < 1.67022) then this indicates that cash turnover partially has a negative and significant effect on Return On Assets; (2) The receivable turnover variable has a significant level of 0.004 <0.05 and a tcount of -3.025. To find the ttable, it was tested at a significance level of 0.05 with df = 61, then obtained a ttable of 1.67022, so that it can be obtained that tcount < ttable (-3.025 < 1.67022) then this indicates that accounts receivable turnover partially has a negative and significant effect on Return On Assets; (3) the variables of cash turnover and accounts receivable turnover have a positive and significant effect on Return On Assets with a significance value of 0.03 > 0.05.